Case Discussion on Palpitation (Panic Disorder with Social Anxiety - Hamzah, Hairul Aini; Ahmad Basri, Nadzirah (2021)
It describes a clinical case scenario of a patient experiencing palpitation due to panic disorder. Relevant investigations are also included